A comprehensive experimental study regarding size dependence on thermal conductivity of graphene oxide nanosheet. (January 2022) - Li, Yifan; Zhang, Tong; Zhang, Yuan; Zhao, Chenggong; Zheng, Niming; Yu, Wei
Abstract: Graphene-based materials have great application prospects in the thermal management field due to their high intrinsic thermal conductivity. Understanding the factors affecting the thermal conductivity of graphene and graphene-based materials is essential for further application of the materials. This study aims to explore the effect of graphene oxide (GO) nanosheet size on its intrinsic thermal conductivity experimentally. By simultaneously characterizing the morphology and thermal conductivity of the nanosheet, an obvious size dependence of thermal conductivity is observed: larger-sized GO nanosheets are preferred to have higher thermal conductivity values. Further detailed morphology and structural analysis identify that this dependence is caused by morphological defects. In addition, whether this dependence at the microscale still exists in practical GO-based materials is also studied. The characterization of thermal conductivity and thermal management performance for macroscopic materials confirms this inheritability. This work clarifies the dependence and its generation principle of thermal conductivity on the GO nanosheet size, meanwhile, it also proves that this dependence still exists when microscopic nanosheets are integrated into macroscopic systems. Highlights: The size dependence on thermal conductivity of graphene oxide (GO) nanosheets was investigated experimentally. The cause of this dependence was studied and explained from the structural and morphological two aspects. Thermal properties of practical GO films and epoxy/GO composite thermal interface materials were characterized. The size dependence on the thermal conductivity of nanosheets at the microscale is still applicable for macroscopic material systems.